A computer-assisted training - Gomes, M.P.S.F (IEEE Transactions on information technology in biomedicine)
A generic framework for a computer-assisted system for both soft tissue endoscopic surgery and surgical training is being researched and developed. The concept demonstrator is a specific system for transurethral prostatic resection (TURF). The main novelty of the research is that it is not confined to an in vitro trainer system. An in vivo monitoring version of the system, for use in the operating theater, is also being researched. This paper presents the framework's structure and design using the Unified Modeling Language. It also discusses and justifies the underlying information technologies chosen to implement this approach. Object-oriented concepts and well-proven mathematical tools have been adopted as the foundation of this research and development. The rationale for having chosen such tools is presented. The objectives are to arrive at a system which is modular, general, and reusable.